A new species of the genus Bothrioplana (Platyhelminthes: Bothrioplanida: Bothrioplanidae) and a new species of the genus Pentacoelum (Tricladida: Bdellouridae) from southern China - He, Yi; Zhao, Jia-Qi; Ning, Wan-Ru; Zhuang, Jie-Yi; Zhang, Yu; Wang, An-Tai (Zootaxa, 2016)
Two new species of turbellarians, Bothrioplana sinensis n. sp., and Pentacoelum sinensis n. sp., were described based on their reproductive behavior, ontogenic development, morphology in whole-mounted and sectioned specimens, and 18S rDNA phylogenetic classification. Bothrioplana sinensis n. sp. represents a newly recorded order in China and the second identified species in the genus Bothrioplana. It is characterized by a pair of spherical-shaped well-developed testes located dorsally behind the pharynx, and the common vas deference located ventrally to the gonopore. Phylogenetic analysis showed that this new species is closely related to parasitic flatworms. Pentacoelum sinensis n. sp. is characterized by two uteri instead of lateral bursae located laterally near the tail end and a lack of connection between the posterior intestinal branches. Each uterus has a ventral receptaculum seminalis (also functioning as bursa copulatrix) which has a muscular vagina externa opening obliquely to the ventral side at the tail end.